Farm management economics - Heady, Earl O. (Prentice-Hall, 1954)
The aim of this subject is for students of agricultural science and agricultural economics to understand the principles of management economics applied to the operation of agricultural business; to understand decision analysis under risk and uncertainty; to be able to model and analyse agricultural systems; to be able to analyse agricultural investment and evaluate the profitability and sources, and business risk and financial risk of alternative resource uses in agricultural businesses; evaluate business growth strategies; and understand agricultural price risk management strategies.